The Prospects for Mathematics in a Multimedia Civilization - Davis, Philip J (The Best Writing on Mathematics 2013, 2014)
First let me explain my use of the phrase “multimedia civilization.”* I mean it in two senses. In my first usage, it is simply a synonym for our contemporary digital world, our click-click world, our “press 1,2, or 3 world”, a world with a diminishing number of flesh-and-blood servers to talk to. This is our world, now and for the indefinite future. It is a world that in some tiny measure most of us have helped make and foster. In my second usage, I refer to the widespread and increasing use of computers, fax, e-mail, the Internet, CD-ROMs, iPods, search